Laundry love : finding joy in a common chore - Richardson, Patric; Miller, Karin B., 1964- (Flatiron Books, 2021)
"Patric Richardson, aka the "Laundry Evangelist," reveals his revolutionary methods for cleaning clothes-and making laundry loads more fun. Doing laundry is rarely anyone's favorite task. But to Patric Richardson, laundry isn't just fun-it's a way of life. After years of running Laundry Camp at the Mall of America for thousands of eager learners, he's ready to share his tips, tricks, and hacks-bringing surprise and delight to this commonly dreaded chore. Sorting your laundry? It's not all about whites and darks. Pondering the wash cycles? Every load, even your delicates, should be washed using express or quick-wash on warm. Facing expensive dry cleaning bills? You'll learn how to wash everything-yes everything-at home. And those basically clean but smelly clothes? Richardson has a secret for freshening those too (hint: it involves vodka, not soap). Changing your relationship with laundry can also change your life. Richardson's handy advice shows us how to save time and money (and the planet!) with our laundry-and he intersperses it all with a healthy dose of humor, real-life laundry stories, and lessons from his Appalachian upbringing and career in fashion. Laundry Love will make you wonder why you ever stressed about ironing, dry cleaning, or (god forbid) red wine spills on your new couch. No matter the issue, Richardson is here to help you make laundry miracles happen-wrinkles and stains be damned"--